2012
DOI: 10.4028/www.scientific.net/amm.157-158.1549
|View full text |Cite
|
Sign up to set email alerts
|

Model and Simulation on Flow and Pressure Characteristics of Axial Piston Pump for Seawater Desalination

Abstract: With cavitation model being considered, a LP (Lumped Parameter) model and a CFD (Computational Fluid Dynamics) model on the flow and pressure characteristics of the axial piston pump for seawater desalination were created. Based on the geometry structure and operating condition of the pump, these two models were numerically calculated and corresponding results were compared and discussed. Both the two models can describe the dynamic flow and pressure characteristics of the pump. The CFD model is accurate and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…From a manufacturing process, it is easier to obtain a small clearance fit between the cylindrical piston and the cylinder hole. From a design perspective, it is easier to ensure that the piston has a sufficient sealing length inside the cylinder hole [19,20]. The Naval Civil Engineering Lab (NCEL) of the United States carried out an in-depth calculation and analysis of the force condition of the gear pump, vane pump, and axial piston pump, and found that the pv value in the friction pair of the axial piston pump is much smaller than those of the other two pumps, which is more conducive to reducing the requirements of wear resistance in the materials [21].…”
Section: Introduction 1development Of Hydraulic Transmission Technologymentioning
confidence: 99%
“…From a manufacturing process, it is easier to obtain a small clearance fit between the cylindrical piston and the cylinder hole. From a design perspective, it is easier to ensure that the piston has a sufficient sealing length inside the cylinder hole [19,20]. The Naval Civil Engineering Lab (NCEL) of the United States carried out an in-depth calculation and analysis of the force condition of the gear pump, vane pump, and axial piston pump, and found that the pv value in the friction pair of the axial piston pump is much smaller than those of the other two pumps, which is more conducive to reducing the requirements of wear resistance in the materials [21].…”
Section: Introduction 1development Of Hydraulic Transmission Technologymentioning
confidence: 99%
“…Pumps' cavitation will increase the flow leakage and pressure impact. Therefore, the discharge pressure has a strong correlation with the cavitation, in contrast to the vibration signal [31,32]. In particular, specific cavitation can damage the surface of the cylinder block and valve plate.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars at home and abroad always focus on performance of the key friction pairs in axial piston pumps and many researchers have focused on these friction pairs. Professors Yang Huayong and Zhou Hua from Zhejiang University mainly studied the key technique breakthrough of friction pairs of axial piston pumps used in seawater and oil [1][2][3]. Professor Yuan Shihua from Beijing Institute of Technology chiefly researched the pressure field and the leakage field of oil film of friction pairs of axial piston pumps [4][5][6].…”
Section: Introductionmentioning
confidence: 99%